Menilik Corporate Social Responsibility Berdasarkan Budaya Songkabala (Studi Pada Chocolicious Kota Makassar) - Riskawati; Muh. Wahyuddin Abdullah; Farid Fajrin (Program Studi Pendidikan Akuntansi, Fakultas Ekonomi, Universitas Negeri Makassar, 2025)
This study aims to determine and understand how to implement and implement Corporate Social Responsibility (CSR) based on Songkabala Culture. The study was conducted in October 2023 at the Chocolicious company located in Makassar City. This study is a qualitative study with a case study approach. The data source used is primary data obtained from interviews and observations. The data analysis used is triangulation of data sources consisting of data reduction, data presentation, and drawing conclusions. The results of the study show that Chocolicious has implemented CSR. The company emphasizes that CSR is an activity or concept carried out by the company which then they are responsible for the social/environmental environment where the company is located. The company carries out its business activities in a more integrated manner, both between the company's goals as a business venture, harmonious relations with society, nature and God